Stress and Deflection Analysis of Locomotive Structural Design: A Case Study on the Shaft of Locomotive CC 203 - I Putu Sindhu Asmara; Indri Ika Widyastuti; Rizqi, Salsabila Intan Nur; Ghagarin Diza Syahraihan; Iklil Huril ‘Ain; Safril Norman Ardiansyah; Basith Baihaqi Amyanfama (P3M Politeknik Perkapalan Negeri Surabaya, 2025)
The increasing demand for railway transportation requires locomotive components to meet high safety and performance standards. One critical component is the shaft, which transmits power from the engine to the wheels and supports the locomotive's total load. This study analyzes the stress and deflection of the CC 203 locomotive shaft using empirical calculations. The shaft, made of ST 52 steel with a ready load of 84 tons and dimensions of 2000 mm in length and 150 mm in diameter, was evaluated based on allowable limits. The results show a maximum stress of 112.27 MPa and a maximum deflection of 4.3 mm, both within the allowable limits of 260 MPa and 5 mm, respectively. These findings indicate that the shaft design meets structural safety and operational reliability requirements. Regular inspections are recommended to maintain optimal performance and prevent material degradation over time.